METODE INTERAKSI PARENTING: UPAYA MENGOPTIMALKAN PENDIDIKAN SISWA SEJAK DINI - Rifai, Moch (Premiere Educandum, 2013)
Parents are obliged to take care of their childrenâs future, especially by Â rendering Â sufficient Â education. Â Children Â are Â believed Â to Â bring about happiness every now and then, who generate familyâs pride up to the almighty judication. Some people are save and some are not in that court, where children will give sigificant contribution in it. Thatâs why the childrenâs well being has become the parents obligation. To bring about Â childrenâs well Â being, parents should also render the good treatments during the life cycle of their children. The main duties of parents for their children are giving them the good names, sending them to the good schools where they can learn religion, and marry them to their good spouses. Psychologically, when children are sent to school for the first time, they will feel that they are put apart from parentsâ Â care, Â so Â that Â may Â of Â them Â have Â to Â go Â difficult Â phase of adjustment. The adjustment includes that of education so as to run as naturally Â as Â possible. Â To Â get Â the Â naturality Â of Â the Â education delegation, teachers and educators are obliged to be able to nurture any value to students as naturally as possible. Parenting model of teaching serves the requirements of teaching children just the way the parrents do, so that it is assumptively effective in teaching elementary students Â by Â taking Â consideration Â on Â the Â psychologial Â aspect Â of children.Â Key words: Â Parenting Â Model Â of Â teaching, Â children Â education optimalization